Matrixed modeling method and entropy generation minimization analysis of heat supply system based on standard thermal resistance. Issue 1 (6th November 2022) - Ju, Chenzhi; Tian, Liang; Hao, Junhong; Yang, Yunxi; Ge, Zhihua; Du, Xiaoze
Abstract: Complex implicit expressions and many intermediate parameters are not conducive to the application of entropy generation optimization to the performance of thermal and energy systems from component and system perspectives. In this paper, we derived matrix heat transport equations of three primary heat exchanger networks according to the heat current method. Based on the matrix equations, we established the matrixed model of a typical heat supply system and obtained the corresponding matrix equation reflecting the power topology structure of the system. Moreover, we derived and reconstructed a single heat exchanger's entropy generation rate expression based on the standard thermal resistance, which was only related to inlet temperatures, structural parameters, and operating parameters. The total system entropy generation rate was then derived and minimized by the Lagrange multiplier method. The optimization results provided the optimal distribution of the mass flow rate of each fluid. Besides, the influence of the heat transfer rate and outer loop inlet temperature on the optimization results revealed that local equipment parameters and conditions could affect the system's minimum entropy generation. The total entropy generation rate decreases by 17.5% when the outer loop inlet temperature was increased from 274 to 280 K. In conclusion, the matrixed modeling and entropy generation analysis are feasible for thermal system modeling and optimization. Abstract : Matrixed a typical heat supply system based on the heat current method, demonstrated the topology structure of the heat supply system through a matrix, derived the entropy generation expression of a single heat exchanger based on the standard thermal resistance, and minimized the entropy generation of the heat supply system using the Lagrange multiplier method.